PEDAGOGICAL USE OF TRANSLATION IN FOREIGN LANGUAGE CLASSROOMS (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2025)
This article argues that translation should be recognized as a valid and effective pedagogical tool in foreign language teaching. Despite the long-standing dominance of monolingual communicative approaches, the strategic use of translation significantly enhances learners’ grammatical awareness, vocabulary acquisition, and metalinguistic reflection. Drawing on the research of Guy Cook, Munise Gultekin, and Dalila Benelhadj Djelloul & Bel Abbes Neddar, the article demonstrates that translation fosters deeper language comprehension and supports balanced bilingual/multilingual competence, particularly in multilingual classrooms. The study concludes that translation, when used selectively and purposefully, serves as a powerful complementary method in contemporary foreign language pedagogy, contributing to both practical outcomes and cognitive development.